Factors affecting customer satisfaction on electronic payment system (E-Payment) for diploma students in Universiti Tun Hussien Onn / Nurul Izza Rahmad - Rahmad, Nurul Izza (2019)
The e-payment system is a means of carrying out transactions or paying for goods and services by electronic means, without the use of cheque or cash. It is also called an electronic payment system or an online payment system. Read on to learn more about it. The electronic payment system has grown more and more over the last decades due to the growing spread of online banking and shopping. As the whole world more technological advances can be seen in the rise of electronic payment systems and payment processing devices. As these increases, improves and ensures increasingly secure online payment transactions, the percentage of cheque and cash transactions will decrease. Therefore, this study focuses on the factors affecting customer satisfaction on electronic payment system (E-Payment) for Diploma students in UTHM, which had previously been implemented any payment manually. The e-payment system aims to provide a platform for student in higher academic institution to process their payment automatically, to assist management in making timely and accurate decision. The methodology that be used is the normality test, reliability test, descriptive analysis, correlation analysis, regression analysis, and frequency analysis will be conducted SPSS 25 package. This research will be expected same with the previous research. After this research have been conducted, the outcome shows the highest factor affecting customer satisfaction on e-payment is the perceived security and additional independent variables can be explored for future research.